Odpowiedź :
3x + 7 + 2x = 22
5x + 7 = 22 / -7
5x = 15 / : 5
x = 15:5
x=3
5x=3x - 6 / -3x
5x - 3x = -6
2x = -6 / : 2
x = -6 : 2
x = -3
8 - 2x = 4x - 4 / - 4x
8 - 2x - 4x = - 4
8 - 6x = -4 / - 8
- 6x = - 4 - 8
- 6x = - 12 / : (-6)
x = - 12 : (-6)
x = 2
mam nadzieje że pomogłam ❤️
5x + 7 = 22 / -7
5x = 15 / : 5
x = 15:5
x=3
5x=3x - 6 / -3x
5x - 3x = -6
2x = -6 / : 2
x = -6 : 2
x = -3
8 - 2x = 4x - 4 / - 4x
8 - 2x - 4x = - 4
8 - 6x = -4 / - 8
- 6x = - 4 - 8
- 6x = - 12 / : (-6)
x = - 12 : (-6)
x = 2
mam nadzieje że pomogłam ❤️